Survival following traumatic thoracic compartment syndrome managed with VV-ECMO. (December 2019) - Amos, Timothy; Yeung, Meei; Gooi, Julian; Fitzgerald, Mark
Abstract: Whilst post-traumatic respiratory failure is the most common indication for use of VV-ECMO in trauma patients, its use in traumatic thoracic compartment syndrome is not yet well described. Thoracic compartment syndrome, a rare complication of thoracic trauma, occurs in the setting of chest wall injuries, impaired chest wall compliance, pulmonary contusions and subsequent high ventilatory pressures. This in turn impairs venous return and increases risk of circulatory arrest due to obstructive shock. This case study describes the successful use of VV-ECMO in a young male with thoracic compartment syndrome following severe blunt chest trauma sustained in a high speed motor vehicle crash. Following brief circulatory arrest, thoracic compartment syndrome was relieved during thoracotomy but reoccurred on chest closure. The use of VV-ECMO for oxygenation permitted lower ventilatory pressures, allowing venous return and primary closure of the thoracotomy. The patient subsequently had an excellent functional outcome. This case describes the successful use of VV-ECMO for a novel indication. The indications for ECMO in thoracic trauma patients continue to evolve.